2016
DOI: 10.1037/a0039023
|View full text |Cite
|
Sign up to set email alerts
|

Children’s narratives of alleged child sexual abuse offender behaviors and the manipulation process.

Abstract: Objective: The aim of the current study is to examine offender behaviors and manipulation tactics described by children using a mixed method analysis. Method: The sample consisted of 95 randomly selected investigative interviews with children (aged 5 to 13 years) in which external evidence indicated a high probability that abuse occurred. An initial qualitative phase that aimed to identify key offender behaviors and manipulation tactics was followed by a quantitative phase, which explored the frequency of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…The concept of traumatic bonding helps to elucidate the process underpinning an 22 GROOMING: A CASE STUDY individual's entrapment in the relationship with the abuser, ensuring compliance, silence and ambivalence about their relationship with the abuser and their own part in the abusive experience. Previous literature highlights the emotionally dependent relationship common in intrafamilial sexual abuse contexts that serves to engender shame and responsibility for the abuse, contributing to an inhibition to disclose the experience (Campbell, 2009;Conte et al, 1989;Craven et al, 2006;Goodman-Brown et al, 2003;Katz & Barnetz, 2015;McAlinden, 2006;Olsen et al, 2007;Smallbone & Wortley, 2001). Less is known about the relational aspects of the grooming process for children abused by extra-familial figures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of traumatic bonding helps to elucidate the process underpinning an 22 GROOMING: A CASE STUDY individual's entrapment in the relationship with the abuser, ensuring compliance, silence and ambivalence about their relationship with the abuser and their own part in the abusive experience. Previous literature highlights the emotionally dependent relationship common in intrafamilial sexual abuse contexts that serves to engender shame and responsibility for the abuse, contributing to an inhibition to disclose the experience (Campbell, 2009;Conte et al, 1989;Craven et al, 2006;Goodman-Brown et al, 2003;Katz & Barnetz, 2015;McAlinden, 2006;Olsen et al, 2007;Smallbone & Wortley, 2001). Less is known about the relational aspects of the grooming process for children abused by extra-familial figures.…”
Section: Discussionmentioning
confidence: 99%
“…Berliner and Conte's (1990) study of 23 child sexual abuse victims aged 10 3 GROOMING: A CASE STUDY to 18 years noted that 57% received special privileges from the abuser and 61% said their abuser had told them that they were 'special'. Katz and Barnetz (2015) investigated grooming in a sample of 95 children aged 5 to 13 years. They found that 68.4% of victims reported that their abuser had manipulated their family.…”
Section: Grooming: a Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, a perpetrator selects a victim and determines how to gain access to that victim (Katz & Barnetz, 2015;McAlinden, 2006;Olsen, Daggs, Ellevold, & Rogers, 2007). In cases of intrafamilial abuse, victim selection may be based on availability (e.g., limited to children residing with the offender).…”
Section: Gaining Access To the Childmentioning
confidence: 99%
“…These behaviors often aim to foster trust and emotional dependency (Craven et al, 2006;Smallbone & Wortley, 2001). Trust is established not only with the child but also with those in the child's environment, including his or her family (Campbell, 2009;Colton et al, 2010;Craven et al, 2006;Katz & Barnetz, 2015;McAlinden, 2006;Olsen et al, 2007). Elliott et al (1995) found that 20% of offenders had gained the trust of the victim's entire family to facilitate the abuse, whereas Smallbone and Wortley (2001) found that 44% of extrafamilial offenders (n = 60) befriended the child's parents.…”
Section: Gaining the Child's Compliancementioning
confidence: 99%